An Exploration of Dystopian Fiction: a Darwinian study of Suzanne Collins's the Hunger Games (2008) - Boumediene,Boumediene; Boumous ,Moufida (Faculty of Letters and Foreign Languages Department of English, 2018)
One of the most important philosophical theories of the late twentieth century is the philosophical inspiration at the time which was the Dystopian or the distressed literature. No investigator of a scientific or literary subject denies that the historical reasoning that justified the existence of such a philosophical view. This research focus on this part dystopia, This philosophical approach was examined in its ideological development and its philosophical dimensions. In this three chapters, this study is going to apply social Darwinism with the creation of its applied model in Suzann Collins's The Hunger Games as it covers the aspects of survivability, competition, and individuality